Die wahre Emanzipation der Frau - Haag, Ella (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1895)
A re-interpretation of the often-bandied-about word "emancipation" to mean improvement of the position of women within the limits of what Haag defines as true womanhood.